Culture Studies: A Bridge from Native Cultural Content to Learners’ Intercultural Competence - Gasparyan, Gayane (Armenian Folia Anglistika, 2005)
In recent decades the use of communicative methods of foreign language teaching has resulted in tangible changes and teaching has focused on the content of public culture and the further development of its intercultural approach. The traditional grammar-translation method with its linguistic restrictions has developed into a wider methodology of teaching based on the model of “language within culture”/ “culture within language”. The use of this model gives preference to the social environment of the given language in the context of its cultural history, norms and values. The idea of the creation of a “New World” forces the learner to feel more confident in different environments of interchangeable cultures and get acquainted with new cultural values. The university teaching course Culture Studies promotes the so-called “cultural competence” and the perception of a foreign language in the extralinguistic features of “the new world” attaching special importance to the development of intercultural knowledge.